Interindustry Energy Demand and Aggregation of Input-Output Tables - Kymn, Kern O. (The Review of Economics and Statistics, 1977)
It is well known that aggregation of input-output tables into smaller orders involves a trade-off between aggregation bias and reduction in the order of the table. The high cost of dealing with 367-order tables and the need for small-order tables in dynamic economic models are important reasons for selecting the optimal aggregation method and specifying the quantitative nature of the trade-off. In this note it is argued that significant aggregation of the 86-order input-output table may be possible without seriously affecting the power of the aggregated table to forecast energy sector output levels. An aggregation system is presented, using the 1963 86-order table in which non-energy sectors are merged while maintaining the energy sectors.